Penerapan Deskriptif Teks dalam Bahasa Inggris pada Karya Mahasiswa Desain Komunikasi Visual - Yohana, Fenti Mariska (Magenta | Official Journal STMK Trisakti, 2019)
Descriptive text is the text that describing a people, a things, and place. It is purpose to describing a person or a thing in a particular. It will be identified the phenomenon of person, place, or thing. Describing parts, qualities, characteristics, etc. So, the students with their artwork can be describing their art by using this text. The students of Visual communication design are going to make a text with their artwork and describe by descriptive text. For example, This picture is a picture at the end of the semester exam in the form drawing course. In the picture there are two apples, one tea glass, a wallet and lurik cloth. To work on this artwork, I need more than two days, because the process is quite difficult, having to attention to parts of the object in detail.